High performance magnetically separable graphene/zinc oxide nanocomposite - Vijay Kumar, S.; Huang , N.M.; Yusoff, N.; Lim, H.N. (2012)
Magnetically separable graphene-Fe2O3/ZnO (G-Fe2O3/ZnO) nanocomposites were prepared by a simple hydrothermal method, using graphene oxide (GO) and Zn(OH)2 as the precursors of graphene and ZnO, respectively and commercially available iron oxide (Fe2O3) as a magnetic material. The nanocomposite materials were characterised by Transmission Electron Microscopy (TEM), Field emission scanning electron microscopy (FESEM), X-ray diffractometry (XRD), Ultravioletâvisible spectroscopy (UVâvis) and Raman spectroscopy. Under natural sunlight, the nanocomposite exhibited excellent photocatalytic degradation of methylene blue (MB). Photoluminescence spectra proved that the high photocatalytic performance of the nanocomposite resulted from the prevention of electronâhole recombination by the effective transfer of electrons between the semiconductors and the graphene. The nanocomposite maintained its ability to degrade MB efficiently, even after 5 cycles of photocatalysis.